Long Term Sequelae of Pediatric Craniopharyngioma – Literature Review and 20 Years of Experience - Cohen, Michal; Guger, Sharon L.; Hamilton, Jill (Frontiers in Endocrinology, 2011)
Craniopharyngioma are rare histologically benign brain tumors that develop in the pituitary- hypothalamic area. They may invade nearby anatomical structures causing significant rates of neurological, neurocognitive and endocrinological complications including remarkable hypothalamic damage. Information regarding long term implications of the tumors and treatment in the pediatric population is accumulating, and treatment goals appear to be changing accordingly. In this review we aim to present data regarding long term complications of craniopharyngioma in children and adolescents and our experience from a large tertiary center. Hypothalamic dysfunction was noted to be the most significant complication, adversely affecting quality of life in survivors. Obesity, fatigue and sleep disorders are the most notable manifestations of this dysfunction, and treatment is extremely difficult. Changes in management in recent years show a potential for improved long term outcomes; we found a trend towards less aggressive surgical management and increasing use of adjuvant treatment, accompanied by a decrease in complication rates.